Congress of Neurological Surgeons Systematic Review and Evidence-Based Guideline on Closure of Myelomeningocele Within 48 Hours to Decrease Infection Risk. Issue 3 (16th August 2019) - Beier, Alexandra D; Nikas, Dimitrios C; Assassi, Nadege; Bauer, David F; Blount, Jeffrey P; Durham, Susan R; Flannery, Ann Marie; Klimo, Paul; McClung-Smith, Catherine; Rehring, Patricia; Tamber, Mandeep S; Tyagi, Rachana; et al.
Abstract: BACKGROUND: Appropriate timing for closure of myelomeningocele (MM) varies in the literature. Older studies present 48 h as the timeframe after which infection complication rates rise. OBJECTIVE: The objective of this guideline is to determine if closing the MM within 48 h decreases the risk of wound infection or ventriculitis. METHODS: The Guidelines Task Force developed search terms and strategies used to search PubMed and Embase for relevant literature published between 1966 and September 2016. Strict inclusion/exclusion criteria were used to screen abstracts and to develop a list of relevant articles for full-text review. Full text articles were then reviewed and when appropriate, included in the evidentiary table. The class of evidence was evaluated, discussed, and assigned to each study that met inclusion criteria. RESULTS: A total of 148 abstracts were identified and reviewed. A total of 31 articles were selected for full text analysis. Only 4 of these studies met inclusion criteria. CONCLUSION: There is insufficient evidence that operating within 48 h decreases risk of wound infection or ventriculitis in 1 Class III study. There is 1 Class III study that provides evidence of global increase in postoperative infection after 48 h, but is not specific to wound infection or ventriculitis. There is 1 Class III study that provides evidence if surgery is going to be delayed greater than 48 h, antibiotics should be given. The full guideline can be found at https://www.cns.org/guidelines/guidelines-spina-bifida-chapter-4 .